The arteries originating from the aortic arch and the patterns of their branches in ground squirrels (Spermophilus citellus) - Aydin, A.; Ozkan, Z. E.; Yilmaz, S.; Ilgun, R. (Czech Academy Agricultural Sciences, 2011)
In this study, the aim was to investigate the anatomy of the aortic arch in ground squirrels (Spermophilus citellus). Five ground squirrels were investigated. The materials were carefully dissected and the arterial patterns of arteries originating from the aortic arch were examined. The brachiocephalic trunk and the left subclavian artery were separated from the aortic arch. The brachiocephalic trunk first gave the left common carotid artery, and then the right subclavian and common carotid artery detached from it. In all the animals examined, at the cranial thoracic entrance and after leaving from this entrance, similar branches arising from the left and right subclavian arteries were the common branch of the internal thoracic artery and the intercostal suprema artery, separate branches as the vertebral and descending scapular arteries and a common branch of the cervical superficial, the cervical profund, the suprascapular arteries and the spinal ramus. After separation of these branches, the continuation of the artery gave the external thoracic artery on the external face of the thoracic cavity and then formed the axillar artery. The axillary artery separated into the subscapular and the brachial arteries. In conclusion, the pattern of arteries originating from the aortic arch and the branches of these arteries were partially similar to what has been observed in red squirrels, and thus differ from other rodents and domestic mammals.
Keywords: arteries; aortic arch; ground squirrels (Spermophilus citellus)